PRESUPOSISI DALAM FILM â€œROBOSAPIEN : REBOOTEDâ€ KARYA SEAN McNAMARA (ANALISIS PRAGMATIK) - RUMENGAN, DAYSANDEY MARIA; KODONG, FENTJE; MITCHEL, HELDA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThÂ coverage of pragmatics presupposition include, speecs act and deixis, in the reaserch, thewriter focuses on one of the the categorie of pragmatics namely presupposition in the film Robosapien : Rebooted by Sean McNamara. The purpose of the reaserch in an attempt to reaserch Â indentify and Â to classify Â the type of presupposition in the film : Robosapien : Rebooted by Sean Â McNamara. In collect Â the data the writer taken the relevan data trough Â the conversation away characters utterance in the movie. Then the writer analyzes the collected data descriptively by Djadjasudarma and in analysis data by using the theory of George Yule. The findings ofÂ this researchÂ shows that presupposition by Yule can be categorized into six types which are : existensial presupposition, factive presupposition, lexical presupposition, structural presupposition, non-factive presupposition, and counterfactual presupposition. the structural presupposition is not used in this film.Keywords : Pragmatic, Presupposition, Robosapien : Rebooted.